Analisis Kinerja Pegawai Dalam Meningkatkan Motivasi Dan Semangat Kerja Pegawai Bapelitbangda Kabupaten Probolinggo - Fahrudin, Fahrudin; Nabilatus Sa'adah, Rashika; Mia Rhianti, Ghefira; kulsum, Ummi; Rusmawati, Rusmawati; Fajriya, Siti; Putri Pratiwi, Metalis; Dwi Pramita, Riska (CV. Ulil Albab Corp, 2024)
Employee performance is an important element in supporting organizational success, especially in the government sector such as the Probolinggo Regency Regional Research and Development Agency (BAPELITBANGDA). Work motivation is defined as an internal drive that encourages individuals to carry out tasks better. This research aims to analyze the influence of motivation and work enthusiasm on employee performance at BAPELITBANGDA. This research uses quantitative methods with a survey approach. Data was collected through a questionnaire distributed to BAPELITBANGDA Probolinggo Regency employees to explore their perceptions of the work environment, job satisfaction and organizational support. Data analysis was carried out using descriptive and inferential statistics, such as regression tests, to identify the relationship between motivation variables, work morale and employee performance. The research results show that motivation and work enthusiasm have a significant influence on employee performance. Factors such as rewards, harmonious working relationships, and a conducive work environment have been proven to increase motivation and work morale, which ultimately contribute to increased productivity and service quality.